Coherent control of the silicon-vacancy spin in diamond - Benjamin Pingault (Nature Portfolio, 2017)
Silicon vacancy centres in diamond have favourable optical properties for use in quantum information processing. Here, the authors demonstrate coherent control of silicon vacancy spins, a prerequisite for the implementation of quantum computing operations.